The Shogun's daughter [compact disc, unabridged] : a novel of Feudal Japan - Rowland, Laura Joh (Rowland, Laura Joh. Sano Ichirō novel., 2013)
Japan, 1704. In an elegant mansion a young woman named Tsuruhime lies on her deathbed. The death of the shogun's daughter has immediate consequences on his regime. Faced with his own mortality and beset by troubles, he names as his heir Yoshisato, the seventeen-year-old son he only recently discovered was his. Until five months ago, Yoshisato was raised as the illegitimate son of Yanagisawa, the shogun's favorite advisor.